Analisis Faktor-Faktor Yang Mempengaruhi Auditor Switching Di Indonesia - Fajar Ramadhan; Husnah Nur Laela Ermaya; Shinta Widyastuti (Institut Bisnis dan Informatika Kesatuan, 2020)
This study is a quantitative study that aims to determine the effect of the audit opinion, financial difficulties, company growth, public accounting firm size, and management changes on auditor turnover. This study uses data on annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The selection of sample criteria is done by purposive sampling technique with predetermined criteria and the data obtained amount to 552 sample data from 138 manufacturing companies and the value of Nagelkerke R square is 12.8%. The results of this study indicate that the size of a public accounting firm has a significant positive effect on auditor turnover, while audit opinions, financial difficulties, company growth, and management changes have no effect on auditor turnover. Keywords: audit opinion, financial difficulties, public accounting firm size, management change, auditor change.